Identifying the relationship between disability and depression among children:A Case Study in Kalutara District, Sri Lanka - Dilhani, E D C; Karunanayake, Danesh (South Asian Journal of Social Sciences and Humanities, 2023)
Purpose of the study: This study mainly aimed to identify the relationship between: (1) disability and depression; and (2) depression and its relations to age, gender, walking ability, self-care dependence, leisure activities, regular exercises, facilitated environment, satisfied peer relationships, and verbal abuse among children with physical disabilities.Methodology: The research design of the study was correlational. A sample of 60 children (n=60) with physical disabilities between 6-15 years were selected by using the purposive sampling method. Quantitative data was collected through a disability scale, depression scale, and a questionnaire on demographic information. Data were analyzed by using IBM SPSS software.Main Findings: Physical disability showed a significant positive relationship with depression. The study were unable to reveal a statistically significant gender difference of depression. The depression scores of participants showed a positive correlation with age while depression was showing negative relationships with ability to walk, self-care dependence, leisure activities, facilitated environment, satisfied relationship with peers, and having goals but not with regular exercises and verbal abuse by peers.Applications of the study: Since the study revealed a potential alarming condition on mental health of children with disabilities, it is that to take prevention initiatives in mental health practice including medico-psychological interventions and social work practices. Further, research findings suggest elaborating existing methodology of educational, health, developmental and policy practices into an active and respectful engagement as well as impactful and responsive outcomes.Originality of the study: The study enabled to extend the established positive relationship between disability and depression among adult population into child population also. Initially the research addresses the lack of comprehensive scientific research on developing disability-inclusive programmes in Sri Lanka. With understanding disability among children as a dimension of diversity, the research highlighted the need of a multi-disciplinary approach to move problem to solution.